2022
DOI: 10.1186/s13613-022-01065-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided internal jugular vein and supraclavicular subclavian vein catheterization in critically ill patients: a prospective, randomized clinical trial

Abstract: Background The aim of this study was to compare the effectiveness and safety of ultrasound-guided out-of-plane internal jugular vein (OOP-IJV) and in-plane supraclavicular subclavian vein (IP-SSCV) catheterization in adult intensive care unit. Methods A total of 250 consecutive patients requiring central venous catheterization, were randomly assigned to undergo either ultrasound-guided OOP-IJV or IP-SSCV cannulation. All catheterizations were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…There is no conflict of opinion among anesthesiologists regarding USG placement of IJV catheterization as many studies have been proved about its success and safety [ 3 , 4 , 17 ]. Our study also showed the same that the success rate is higher in the real-time ultrasound technique, but using ultrasound pre-location technique and anatomical landmark technique has a much lower success rate.…”
Section: Discussionmentioning
confidence: 99%
“…There is no conflict of opinion among anesthesiologists regarding USG placement of IJV catheterization as many studies have been proved about its success and safety [ 3 , 4 , 17 ]. Our study also showed the same that the success rate is higher in the real-time ultrasound technique, but using ultrasound pre-location technique and anatomical landmark technique has a much lower success rate.…”
Section: Discussionmentioning
confidence: 99%
“…If necessary, ultrasound can be called in to assist, which can help identify early ectopic catheters, and adjustments can be made to ensure the catheter tip is in the correct position. 14…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound-guided supraclavicular subclavian vein approach shows promising results, with shorter puncture time 29.8 s, 4% fewer attempts needed, and less guidewire misplacement – 0% in comparison to the ultrasound-guided infraclavicular approach (46.9 s, 22.2%, and 8.9%, respectively) [ 35 ]. Moreover, it has a higher success rate (98.4%), shorter insertion time (43.9 s), fewer needle redirection attempts (0.69), and less guidewire advancing difficulties – 2.4% in comparison to ultrasound-guided jugular vein (96.8%, 53.1 s, 1.17, 27.4%, respectively) [ 36 ]. The ultrasound-guided supraclavicular subclavian vein approach could potentialy be identified as the simplest route to the central vein, but the advantageous antimicrobial pattern and patient comfort still need to be proven.…”
Section: Discussionmentioning
confidence: 99%